RESPON INVESTOR ATAS SINYAL LABA, PELUANG BERTUMBUH, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2014-2018 - Jessica Jessica; Ari Hadi Prasetyo (Jurnal Akuntansi, 2019)
This study aims to examine the financial performance of public companies viewed from the effects of earnings persistence, growth opportunities, profitability, capital structure, and company size that affect market response to earnings information measured using earnings response coefficient (ERC). From the perspective of the Signaling theory, management releases information related to the company's performance for investors regarding the company's actual fundamental condition. Companies that have a competitive advantage and good financial performance, have the potential to generate high profits because the company able to manage its resources in the perspective of Resources Based Theory, but in the context of Agency Theory the agent's relationship with the principal, causes agency problems due to differences in interests caused agency conflict. This study uses a sample of 31 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. Based on the results of the regression analysis, it can be concluded that there are enough dependent variables together that significantly influence the earnings response coefficient. The results of this study indicate enough evidence is found that earnings persistence has a positive effect on ERC. Also, growth opportunities influence ERC and give a negative direction. While the capital structure, profitability, and size of the company were not found enough evidence of influence on ERC.Keywords: earnings persistence, growth opportunities, capital structure, profitability, company size, and earnings response coefficient.